Simplification of Arabic Preparatory Classes Through an Intensive Learning in Higher Education - Slamet Riyadi; FNU Rozaanah (Indonesian Journal of Arabic Studies, 2023)
Purpose: This study seeks to describe an intensive Arabic learning model that has been tested at As-Sunnah Islamic College for three months with the same success rate as one- to two-year language preparation courses for university students. Design/ methods/approach: this research uses a qualitative naturalistic approach where the research is carried out naturally following the program implemented in the field without manipulating the existing variables. Furthermore, the data is described and compared objectively with data from existing language preparation programs. Findings: The Intensive Course, also known as Daurah Mukatssafah, consists of two primary activities. First, intensively study the Arabic book Baina Yadaik, beginning with volume 1 and ending with volume 6, in classes led by multiple lecturers per class. Second, language proficiency utilizes an immersion model outside of the classroom. The results demonstrated a considerable increase in students' Arabic proficiency, equivalent to one year's worth of learning in the Language Preparation Course.Â Â